Calculation of heating laminar fluid flow with variable heat transfer coefficient on the surface of circular channel - U. V. Vidin; V. S. Zlobin; R. V. Kazakov (Известия высших учебных заведений: Проблемы энергетики)
An approximate analytical method for calculating temperature distribution in laminar flow, that moving in cylindrical channel. In case where the heat transfer coefficient on the outer surface of arbitrary function on the axial coordinate. Special integral transformation turns the task boundary condition to linear second kind boundary condition. In this case can be applied a classical mathematical solution.